2013
DOI: 10.3109/08820538.2012.760624
|View full text |Cite|
|
Sign up to set email alerts
|

Unilateral Acute Dacryocystitis Associated with Oculoglandular Tularemia: A Case Report

Abstract: Oculoglandular tularemia is not only suspected in cases who complain of fever, cervical lymphadenopathy and purulent conjunctivitis, it should also be suspected in cases who are admitted to the hospital with acute dacryocystitis, which is a rare component of oculoglandular syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…28 Interestingly, poor case outcome for EEE was correlated with the length of the prodromal illness phase, with those patients with the shortest prodrome having the worst long-term followup symptoms. This could be because of variation in neuroinvasiveness, fitness, or virulence of different strains of virus, 29 because of host factor variability, 30 or exposure to substances that damage the blood-brain barrier and enhance neuroinvasiveness. 31 In addition to long-term health effects resulting from encephalitis or encephalomyelitis, there are case reports that include sepsis and myocarditis in addition to neurological symptoms.…”
Section: Screening Before and After Testingmentioning
confidence: 99%
“…28 Interestingly, poor case outcome for EEE was correlated with the length of the prodromal illness phase, with those patients with the shortest prodrome having the worst long-term followup symptoms. This could be because of variation in neuroinvasiveness, fitness, or virulence of different strains of virus, 29 because of host factor variability, 30 or exposure to substances that damage the blood-brain barrier and enhance neuroinvasiveness. 31 In addition to long-term health effects resulting from encephalitis or encephalomyelitis, there are case reports that include sepsis and myocarditis in addition to neurological symptoms.…”
Section: Screening Before and After Testingmentioning
confidence: 99%
“…Although tularemia in pregnancy has recently been increasingly reported [2][3][4][5], the number of pregnant women among the 393 patients with tularemia reported by Mengeloglu et al was not indicated. Unfortunately, even though it is vital for the pregnant woman and the fetus to receive the optimal medical treatment, there is not enough reported data on this subject.…”
mentioning
confidence: 99%
“…However, the dacryocystitis was drained surgically through an incision and a ciprofloxacin-impregnated sponge was placed in the wound tissue daily over the first week. She was also treated with oral amoxicillin/clavulanic acid [5]. Both patients recovered without any complication.…”
mentioning
confidence: 99%
See 2 more Smart Citations